Assessment of greenhouse gas emissions and environmental impacts in the manufacturing process of thermoelectric coolers: A life-cycle impact perspective - Hyo Young Kim; Jeong Eun Kim; Daehyun Wee (Heliyon)
A path to carbon neutrality requires the development of refrigeration units that use no refrigerant or emit less greenhouse gas (GHG), such as Thermoelectric coolers (TECs). Using the life cycle inventory assessment (LCIA), the environmental impacts of the manufacturing process of TECs were analyzed, including greenhouse gas emissions, human carcinogenic toxicity (HCT), terrestrial ecotoxicity (TE), freshwater ecotoxicity (FE), mineral resource scarcity (MRS), and fossil resource scarcity (FRS). The alumina plate manufacturing process produces the most GHG emissions because it uses a lot of electricity in the sintering process. The type of energy source significantly affects GHG emissions, HCT, FE, and FRS but has only a limited impact on TE and MRS. Also, TE, FE, and MRS are affected by the mineral resources used to manufacture the legs.Also, GHG reductions in the manufacturing process have been predicted based on Korea's electricity supply and demand plan for 2030. According to the plan, fossil energy is expected to decrease in 2030 compared to 2021, while renewables and nuclear power are expected to increase. For every 1 MWh of cooling amount, GHG emissions are predicted to decrease from 2.9 kg CO2-eq in 2021 to 1.95 kg CO2-eq in 2030 with a greener energy mix.In addition, generating 2.1 % with green hydrogen would reduce total GHG emissions by 1.7%p more than grey hydrogen generation. Increased use of nuclear and hydrogen energy and decreased use of coal energy are likely to be the biggest drivers of reductions. This study suggests that alternatives to alumina plates that are more environmentally friendly should continue to be explored along with process improvements such as fast heating rate or sintering aids.